Antimicrobial activity and chemical composition of essential oil of Malaysian Etlingera elatior (Jack) R.M. Smith flowers - Darnis, Deny Susanti; Awang, Nurul Aina; Qaralleh, Haitham; Sheikh Mohamed , Hassan Ibrahim; Attoumani, Nissad (Taylor and Francis Group, 2013)
The composition of the essential oil obtained from the flowers of Etlingera elatior (Jack)R.M. Smith was analysed using GC-MS. The antimicrobial activity of the essential oil was conducted using disc diffusion method,determination of minimum inhibition concentration (MIC) and minimum bactericidal/fungicidal concentration (MBC or MFC). The essential oil of the flowers of E. elatior was found to be active against Staphylococcus aureus, Bacillus cereus, Candida albicans and Cryptococcus neoformans. The GC-MS data showed the main components found in the essential oil were identified as 1-decanol (16.27 %), dodecanal (16.87 %), n-dodecyl acetate (16.40 %), cis-9-tetradecen-1-ol (16.29 %) and 1-hexadecanol (16.34 %).